Fundamental application of Internet of Nano Things - Das, Parika; Farihah, Rumnaz (Brac University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.